Craving, Fundamental Passion of the Poetic Subject in Los crepúsculos del jardín by Leopoldo Lugones (Anclajes, 2026)
Leopoldo Lugones's second book of poems, Los crepúsculos del jardín, remains relevant: it represents an extreme of Modernism (Kirkpatrick) and, moreover, is foundational to later poetry in the second half of the 20th and into the 21st century in Argentina (Gramuglio; Vignoli). From the semiotics of passions (Greimas and Fontanille), craving becomes the structuring passion of subjectivity, oscillating between obsession and apathy. From this polarization arises a strong internal tension, illuminated by the lens of eroticism (Bataille) and the paroxysm of desire (Klein). The self, always unsatisfied, constantly brushes against emptiness: in the restraint of Los crepúsculos del jardín and in the exaggerated giving and demanding nature of the posthumous collection Cancionero de Aglaura. This craving can be read as the characteristic passion of the Lugonian subject as a whole.
Keywords: Literary Criticism; Argentine Poetry; 19th and 20th Centuries; Leopoldo Lugones